2002
DOI: 10.1345/aph.1a254
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing or Switching Selective Serotonin-Reuptake Inhibitors

Abstract: Adverse effects are the most frequent reason for discontinuing or switching SSRIs within the first 3 months of treatment. Patients are more likely to continue taking their antidepressant if they fully understand how long to take the medication. Informing patients of potential adverse effects does not appear to prevent premature discontinuation, but may increase the patient's awareness and reporting of mild to moderate adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(70 citation statements)
references
References 14 publications
1
65
1
3
Order By: Relevance
“…Patients often do not wish to stay on their medication long enough to give the SSRI an adequate trial, but instead stop the medication due to the side effects and multiple visits required. 53 The intervention took place in individual format chairside, while the patients were being dialyzed. The protocol consisted of ten 60-minute weekly sessions spread over a maximum of 3 months.…”
Section: Interventionmentioning
confidence: 99%
“…Patients often do not wish to stay on their medication long enough to give the SSRI an adequate trial, but instead stop the medication due to the side effects and multiple visits required. 53 The intervention took place in individual format chairside, while the patients were being dialyzed. The protocol consisted of ten 60-minute weekly sessions spread over a maximum of 3 months.…”
Section: Interventionmentioning
confidence: 99%
“…For the majority of relevant diagnoses, regular intake is recommended for months or even longer (Gaebel and Falkai, 2001). However, despite the positive profile of SSRIs, premature discontinuation is common and frequently discussed to account for nonresponse and relapse (Bull et al, 2002). Sexual dysfunction is a typical side effect of SSRI treatment (Serretti and Chiesa, 2009) that conditions discontinuation and may represent the most clinically relevant side effect among patients in their twenties or thirties (Bishop et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dysfunction is a common and disconcerting sideeffect of SSRIs that influences a patient's desire to continue long-term antidepressant treatment (Bull et al, 2002;Clayton et al, 2002;Montejo et al, 2001). Despite clinical study reports summarized in prescriber information sheets indicating the emergence of sexual difficulties in o15% of subjects, most investigations of this topic show that the real incidence of sexual side-effects subsequent to SSRI initiation is between 20 and 70% (Clayton et al, 2002;Montejo-Gonzalez et al, 1997;Montejo et al, 1996Montejo et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual side-effects from these medications are of significant clinical importance, particularly in young, sexually active patients. Previous research has shown that approximately 40% of persons starting an SSRI will either discontinue or switch medications owing to an adverse event (Bull et al, 2002). Of persons discontinuing or switching SSRIs due to adverse events, over one-third listed sexual side-effects as either primary or secondary reasons for treatment cessation (Bull et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation